Risk Management for 4-H Youth Development Work: Transportation - Dale Pracht; Marilyn Norman; Kate Fogarty; Jean Hink (EDIS, 2010)
4H10.7, a 2-page fact sheet by Dale Pracht, Marilyn Norman, Kate Fogarty, and Jean Hink, is part of the Risk Management for 4-H Youth Development Work series. It describes the possibility of risks when transporting participants during 4-H activities. Includes references. Published by the Florida 4-H Youth Development Program, August 2010.